THE INFLUENCE OF CINEMA ON THE SPIRITUAL RISE OF THE INDIVIDUAL AND ITS SOCIAL FUNCTIONS - Jabborova Aziza G’ayratovna (Western European Studies, 2025)
The article focuses on the impact of cinema on individual spirituality and the analysis of its social functions. In modern society, the consequences of increasing factors affecting personality spirituality, subordination of cinema to market relations are studied. It has been analyzed that cinema, like all types of art, performs certain social functions, the existence of identities and differences between them.
Keywords: personality spirituality; film studies; degumanization